‘Tsatsu tsɛ̃ɛ̃ bo…’: Societal reactions to male infertility among the Ga’s in Ghana - Rosemond Akpene Hiadzi; Godwin Banafo Akrong (PLoS ONE, 2025)
Patrilineality plays a significant role in determining and confirming an individual’s family membership based on their father’s lineage. However, despite the importance of patrilineality in some societies, male infertility—which contributes significantly to infertility and accounts for half of all cases—has emerged as a significant concern. Thus, the study explores societal reactions to male infertility in Krokobite, a suburb of Accra, which is a predominantly Ga-speaking and patrilineal society. The study adopted a qualitative approach, utilizing in-depth interviews (24), focus group discussions (9), and key informant interviews (3). The study’s findings primarily attribute infertility to women, identifying blood incompatibility between couples as a contributing factor in some situations. The findings additionally show that men who are unable to have children or who delay having children face persistent teasing from their peers, who seek to encourage them to join the group of “responsible” men in society by having a child. The study further concludes that the concept of reproductive masculinity is evident in how participants regard males as fertile and less prone to reproductive harm. However, it does not show a significant relationship between reproductive masculinity and the role of fathers in identifying the cause of infertility in a relationship.